Electronic and thermal transport properties of the metallic antiferromagnet MnSn2. Issue 3 (5th January 2023) - Yang, Mingge; Wang, Ziyue; Li, Jiangxiao; Hong, Bin; Du, Yinchang; Wei, Wensen; Wang, Ruilong; Liu, Fengguang; Zu, Lin
Abstract : We report the structure, magnetic and electrical/thermal transport properties of the antiferromagnet MnSn2 . Abstract : We report the structure, magnetic and electrical/thermal transport properties of the antiferromagnet MnSn2 . Importantly, the existence of the two antiferromagnetic states below T N2 (∼320 K) is confirmed by magnetism and electrical transport measurements. An unsaturated positive magnetoresistance up to 150% at ∼9 T was observed at 5 K, whereas the magnetoresistance becomes negative in the whole range at high temperatures ( T > 74 K). Systematic investigations of the Hall transport and thermoelectric properties reveal that the hole-type carriers are the majority carriers in MnSn2 . The kink around 320 K in the Seebeck coefficient originates from the effect of the antiferromagnetic phase on the band structure, while the pronounced peak around 231 K is attributed to the phonon-drag effect. The results suggest that the spin arrangement plays a vital role in the magnetic, electrical, and thermal transport properties in MnSn2 .